Partial night lighting may reduce the physiological impact of artificial light at night on captive zebra finches - Reid, Rachel R.; Dawson, Neal; Duncan, Eleanor; Gillespie, Robert; Mitchell, Christopher; Branston, Claire J.; Capilla-Lasheras, Pablo; Boonekamp, Jelle; Dominoni, Davide M. (Frontiers in Physiology, 2025)
BackgroundArtificial light at night (ALAN) continues to increase at an unprecedented rate globally every year. ALAN can disrupt circadian rhythms and cause behavioural and physiological changes which may have knock on effects for health, yet we still understand very little about these effects. It is becoming increasingly important to investigate potential mitigation strategies, through understanding what aspects of ALAN negatively impact wildlife health.MethodsHere we present the results of an experiment where we investigated the impact of ALAN on various health biomarkers in 44 captive adult zebra finches (Taeniopygia guttata) over the course of 4 months. The health biomarkers measured included glucose concentration, change in relative telomere length, malondialdehyde, and antioxidant capacity of plasma. The birds were separated into three treatment groups consisting of 13–16 individuals and were either exposed to full light at night, partial light at night or darkness (control).ResultsWe show that exposure to full light at night impacted the circadian pattern of glucose levels, with glucose concentrations remaining elevated later into the night compared to the control group. Full light at night also accelerated telomere shortening. However, the relationship between telomere length and treatment only became significant when the partial light at night treatment group was removed and should therefore be interpreted with caution. These effects were not observed under partial light at night.ConclusionOur findings suggest that partial night lighting may mitigate some of ALAN’s negative impacts on wildlife health. This approach could be a valuable tool in future strategies to reduce the ecological effects of light pollution in urban environments and should be investigated further.